2019
DOI: 10.1016/j.mssp.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring strain caused by ion implantation in GaN

Abstract: The reaction of GaN to ion implantation was studied in thin films grown on the a-plane (non-polar) and on the c-plane (polar). 300 keV argon ions were implanted at room temperature to fluences ranging from 5 × 10 12 atoms/cm 2 to 8 × 10 15 atoms/cm 2 . The structural analysis was performed using Rutherford Backscattering/Channeling and X-Ray Diffraction. The results allow to reinforce the suggestion that perpendicular strain caused by ion implantation is the driving force behind defect transformation processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…The satellite peaks shifted towards lower 2θ angles, indicating that the vertical lattice strain gradually increased. [12] It can be observed that the increasing Tb 3þ injection dosage leads to a continuous enhancement of atomic interactions and an increase in compressive stress perpendicular to the sample surface, which is consistent with the results of Raman spectra.…”
Section: Doi: 101002/pssa202300625supporting
confidence: 87%
See 1 more Smart Citation
“…The satellite peaks shifted towards lower 2θ angles, indicating that the vertical lattice strain gradually increased. [12] It can be observed that the increasing Tb 3þ injection dosage leads to a continuous enhancement of atomic interactions and an increase in compressive stress perpendicular to the sample surface, which is consistent with the results of Raman spectra.…”
Section: Doi: 101002/pssa202300625supporting
confidence: 87%
“…Mendes et al demonstrated that increased vertical lattice strain can be identified by the offset of satellite peaks towards lower 2 θ angles. [ 12 ] In Figure 2d, satellite peaks appeared on the left side of the diffraction peak because of lattice damage caused by the Tb 3+ injection. The satellite peaks shifted towards lower 2 θ angles, indicating that the vertical lattice strain gradually increased.…”
Section: Resultsmentioning
confidence: 99%
“…XRD allows for measuring the lattice parameters of crystals with very high resolution and is thus the technique of choice to assess strain induced by implantation defects. It is now commonly accepted that strain is one of the main driving forces for defect transformation from point defects to extended defects and eventually to amorphization [38,60,61]. Indeed, the results, presented in Section 3.1, showed that these defect transformations take place even at 15 K, suggesting that thermal effects are negligible, which agrees with the almost identical damage build-up curves at 15 K and room temperature [35].…”
Section: Ion Implantation In Gan Nanowiressupporting
confidence: 73%
“…The MROX code, as recognized software for the simulation of X-ray diffraction measurements, was used in X-ray diffraction single reflection mode. 53–58 The simulations considered pseudomorphic growth, i.e. , the Ge in-plane lattice parameter equals the ones from the Si substrate and Si buffer layer.…”
Section: Experimental Results and Mrox Simulationsmentioning
confidence: 99%